Sex work involvement among women with long-term opioid injection drug dependence who enter opioid agonist treatment - Marchand Kirsten; Oviedo-Joekes Eugenia; Guh Daphne; Marsh David C; Brissette Suzanne; Schechter Martin T (BMC, 2012)
Abstract Background Substitution with opioid-agonists (e.g., methadone) has shown to be an effective treatment for chronic long-term opioid dependency. Survival sex work, very common among injection drug users, has been associated with poor Opioid Agonist Treatment (OAT) engagement, retention and response. Therefore, this study was undertaken to determine factors associated with engaging in sex work among long-term opioid dependent women receiving OAT. Methods Data from a randomized controlled trial, the North American Opiate Medication Initiative (NAOMI), conducted in Vancouver and Montreal (Canada) between 2005-2008, was analyzed. The NAOMI study compared the effectiveness of oral methadone to injectable diacetylmorphine or injectable hydromorphone, the last two on a double blind basis, over 12 months. A research team, independent of the clinic services, obtained outcome evaluations at baseline and follow-up (3, 6, 9, 12, 18 and 24 months). Results A total 53.6% of women reported engaging in sex work in at least one of the research visits. At treatment initiation, women who were younger and had fewer years of education were more likely to be engaged in sex work. The multivariate logistic generalized estimating equation regression analysis determined that psychological symptoms, and high illicit heroin and cocaine use correlated with women's involvement in sex work during the study period. Conclusions After entering OAT, women using injection drugs and engaging in sex work represent a particularly vulnerable group showing poorer psychological health and a higher use of heroin and cocaine compared to women not engaging in sex work. These factors must be taken into consideration in the planning and provision of OAT in order to improve treatment outcomes. Trial Registration NCT00175357.